Modeling of an Integrated Workstation Environment for Occupational Safety and Health Application - Isa, Halim (CRC Press Taylor & Francis Group, 2011)
Ergonomics evaluation tools appear to be useful means to analyze occupational risk factors, however they are presented as an isolated tool. Hence ergonomics practitioners could not obtain total solution to solve the occupational safety and health problems. The objective of this study is to integrate selected ergonomics evaluation tools in a Knowledge-Base Decision Support System (KBDSS) to provide detail information to ergonomics practitioners in managing ergonomics hazards. The Model Oriented Simultaneous Engineering System (MOSES) was adopted to develop the information architecture. The value of the developed KBDSS is demonstrated through a case study in a manufacturing environment.